Formulation Development and Evaluation of Atorvastatin Soy Lecithin Solid Dispersion A Promising Approach for Solubility Enhancement - Lale, Madhuri; Taksande, Jayshree; Hirave, Keshav; Jaiswal, Nupur; Gupta, Radhika; Qutub, Mohammad; Tatode, Amol; Umekar, Milind (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Hyperlipidaemia remains a significant contributor to cardiovascular disorders, with statins being the primary therapeutic agents for its management. However, the clinical efficacy of these drugs, particularly atorvastatin, a statin with an extended plasma half-life of 18-24 hr is hindered by poor aqueous solubility, which limits bioavailability. This study aimed to address this limitation by enhancing the solubility and dissolution profile of atorvastatin through advanced formulation strategies. Materials and Methods: A solid dispersion approach utilizing phospholipids as a matrix-forming agent was employed to improve drug solubility. The dispersion was synthesized via solvent evaporation, with methanol-ethanol (1:1) selected as the optimal solvent system based on preliminary solubility assessments. Adsorbents and disintegrants were integrated to optimize flowability and dissolution kinetics. The impact of varying phospholipid-to-drug ratios on performance was systematically evaluated. Results: The formulation with a 2:3 drug-to-phospholipid ratio demonstrated superior outcomes, achieving a solubility of 614±24 μg/mL and 91.2±2.27% dissolution within 90 min. Advanced analytical techniques, including Differential Scanning Calorimetry (DSC) and powder X-ray Diffraction (XRD), confirmed the amorphous dispersion of atorvastatin within the phospholipid matrix. Subsequently, an orodispersible tablet was developed using the optimized dispersion, exhibiting favorable pharmaceutical attributes. Conclusion: The integration of phospholipids in solid dispersion systems presents a viable strategy to overcome solubility challenges associated with atorvastatin, offering a scalable and effective solution for enhancing its therapeutic potential.
Keywords: Solid dispersion; Atorvastatin; Soy Lecithin; Solubility Enhancement; Orodispersible Tablets.